Prevalence of dyspepsia: the epidemiology of overlapping symptoms. - Grainger, S. L. (BMJ Group, 1994)
Studies of the epidemiology of dyspepsia have been complicated by the use of different symptom definitions, subject populations and time frames of investigation. Published figures for the prevalence of dyspepsia vary from 20% to 40%, of which perhaps only a quarter can be attributed to peptic ulcer disease. General practitioners see only a fraction of the dyspepsia within the community, the majority of which is either ignored or treated by self-medication. However, dyspepsia still accounts for about 3-4% of all general practice consultations and for about 14% of all patients attending. In about half of all cases, even extensive investigation reveals no underlying organic lesion. There has been much recent interest in the clinical value of grouping dyspeptic symptoms into particular subtypes. These have been called ulcer-like, dysmotility-like and reflux-like. Although these patterns have descriptive value, there is no evidence that they result from discrete pathophysiological processes. Indeed, studies both in general practice and in the community show a large degree of overlap between them.